Investigation of Bluff Body Shape Variation on Enhancing Heat Transfer Performance of Backward-Facing Step Flow - Fitri Wahyuni; Rizki Aldi Anggara; James Julian; Riki Hendra Purba; Fathin Muhammad Mahdhudhu; Elvi Armadani; Nely Toding Bunga (Fakultas Teknik Universitas Pancasila, 2026)
The control of flow separation phenomenon is a challenge that has attracted much attention from researchers in the context of heat and mass transfer. This phenomenon negatively affects heat transfer performance in thermal management applications. Flow control devices play a crucial role in minimizing the effects of flow separation. One of the fundamental geometries that supports understanding in flow separation control is the backward-facing step. Therefore, this study aims to investigate the utilization of bluff body shape variations, including cube, cylinder, and diamond shapes, as passive flow control devices on heat transfer performance in backward-facing step flow. The present study used a Computational Fluid Dynamics solver, followed by a variation of the Reynolds number, 50 ≤ Re ≤ 400. Computational results show that the bluff body significantly reduces the primary recirculation zone and compresses the thermal boundary layer, strengthening the temperature gradient and improving the heat transfer rate. The cube variation demonstrates the optimal thermal performance, exhibiting an augmentation in the average Nusselt number of up to 28.15% at Re = 400, resulting the highest overall Performance Evaluation Criterion.